2017
DOI: 10.1111/jcmm.13436
|View full text |Cite
|
Sign up to set email alerts
|

Combination of arsenic trioxide and Dasatinib: a new strategy to treat Philadelphia chromosome‐positive acute lymphoblastic leukaemia

Abstract: Tyrosine kinase inhibitors (TKIs) have significantly improved the prognosis of Philadelphia chromosome‐positive acute lymphoblastic leukaemia (Ph+ ALL), one of the most common and aggressive forms of haematological malignancies. However, TKI resistance has remained an unsolved issue. In this study, we investigate the impact of adding arsenic trioxide (ATO) on the action of Dasatinib, a second‐generation TKI, in Ph+ ALL. We show that ATO cooperates with Dasatinib in both TKI‐sensitive and resistant Ph+ ALL cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…These findings further strengthen the contention that AMPK activation impacts on the UPR, leading to increased vulnerability to ER stress in ALL cells. Other strategies aimed to unleash proapoptotic UPR in ALL cells involved the use of Pevonedistat ® (Takeda Oncology, Cambridge, MA, USA), an inhibitor of neural precursor cell expressed, developmentally down-regulated 8 (NEDD8)-activating enzyme that targets E3 cullin-RING ligases-dependent proteasomal protein degradation [150]; of CX-4945, an inhibitor of casein kinase 2 (CK2) signaling [151], also in combination with bortezomib [152]; of the natural acyclic sesquiterpene alcohol, farnesol [153]; of sphingosine kinase inhibitors [154]; of a phosphine copper(I) complex [Cu(thp)4][PF6] [155]; of a combination of ATO and dasatinib that was effective in Ph + B-ALL cells [156]; of epigallocatechin gallate, a green tea extract, that binds to the ATP-binding site of GRP78, thereby leading to a conformational conversion into its inactive oligomeric form [123]. All these studies demonstrated that ALL cells are prone to ER stress/UPR-mediated apoptosis via a variety of signaling pathways/mechanisms.…”
Section: Therapeutic Strategies For B-all and T-allmentioning
confidence: 99%
“…These findings further strengthen the contention that AMPK activation impacts on the UPR, leading to increased vulnerability to ER stress in ALL cells. Other strategies aimed to unleash proapoptotic UPR in ALL cells involved the use of Pevonedistat ® (Takeda Oncology, Cambridge, MA, USA), an inhibitor of neural precursor cell expressed, developmentally down-regulated 8 (NEDD8)-activating enzyme that targets E3 cullin-RING ligases-dependent proteasomal protein degradation [150]; of CX-4945, an inhibitor of casein kinase 2 (CK2) signaling [151], also in combination with bortezomib [152]; of the natural acyclic sesquiterpene alcohol, farnesol [153]; of sphingosine kinase inhibitors [154]; of a phosphine copper(I) complex [Cu(thp)4][PF6] [155]; of a combination of ATO and dasatinib that was effective in Ph + B-ALL cells [156]; of epigallocatechin gallate, a green tea extract, that binds to the ATP-binding site of GRP78, thereby leading to a conformational conversion into its inactive oligomeric form [123]. All these studies demonstrated that ALL cells are prone to ER stress/UPR-mediated apoptosis via a variety of signaling pathways/mechanisms.…”
Section: Therapeutic Strategies For B-all and T-allmentioning
confidence: 99%
“…Sustained JNK activation can induce apoptosis. [ 20 , 21 ] To detect the apoptotic roles of JNK signaling pathways in BLIN-1 cells, we used the specific JNK inhibitor SP600125 to block JNK phosphorylation and its downstream signaling [ 22 ]. The results showed that 40 μM SP600125 blocks the increase in C-MYC expression and PARP cleavage induced by CpG 685 for 24 h (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The miR‐214 level was significantly lower in coronary artery disease patients compared with that in controls, which may be a biomarker for alerting severe coronary artery disease 24 . Also, miR‐214‐3p was downregulated in HAECs stimulated with ox‐LDL 25,26 …”
Section: Discussionmentioning
confidence: 95%